PROJECT ANALYSIS OF A TWO-CHANNEL TECHNOLOGICAL INDUCTION ACCELERATOR FOR COMMERCIAL APPLICATION - Kulish, V.V.; Chemerys, V.T.; Gubanov, I.V.; Podvorny, O.O. (Proceedings of National Aviation University (archive), 2005)
The results of the project analysis of an electron two-channel induction accelerator are presented in the paper. Determination technological parameters of the accelerator blocks is carried out. Apart from that, general characteristics of the installation proposed for practical realization are estimated. It is shown, in particular, that a commercial system of high-efficiency and relatively compact can be constructed for purification of wastewater and natural water on the basis of the proposed accelerator.